Planos ótimos de cultivos no projeto de irrigação de bebedouro, município de Petrolina, Pernambuco - M Reis, Maurílio; Ribon, Miguel; Paniago, Euter; Coelho de Alvarenga, Sonia (Revista Ceres, 2025)
Pernambuco. The central objective was to develop an optimum crop plan (in terms of cropping proportions) at plotlevel. Linear programming was used as a tool to determine the combination of activities that maximize net returns to the farmer’s fixed resources. The importance of this study is based on the fact that the determination of optimum crop plans which indicate the best use of: ‘available resources is instrumental for the selected area and other areas in the São Francisco Valley that operate under similar conditions.